Decision Support System to Determine the Eligibility of Overseas Workers at the Employment and Transmigration Office of Sel Regency with the Analytica Hierarchy Process (Ahp) Method - Angga Dwi Supardi Putra, Edo; Yupianti, Yupianti; Sartika, Devi (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Selection for the placement of Indonesian Migrant Workers (TKI) is an activity that is often carried out by Manpower and Transmigration Office of Seluma Regency to find prospective workers abroad who are suitable to be sent and placed there. In determining the Best Worker Candidates, there are criteria from the Manpower and Transmigration Office of Seluma namely there are four criteria, including Age, Education, Language Mastery and Medical Check Up. The research method used in this research is the Analytical Hierarchy Process (AHP) method. AHP can help in making decisions on complex problems by simplifying the process. This system can help decision makers in determining the best prospective workers quickly and accurately. It is hoped that in the future we will be able to use this application in determining the Best Worker Candidates at Manpower and Transmigration Office of Seluma Regency, as well as maintaining the application that the author has previously created so that in the future it can be used by Manpower and Transmigration Office of Seluma Regency.